The complete mitochondrial genome of Reticulitermes ovatilabrum (Isoptera: Rhinotermitidae) - Chen, Tong (Mitochondrial DNA B Resour, 2021)
The mitochondrial genome of the Reticulitermes ovatilabrum is 15,913 bp in length and encodes 37 genes including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), 2 ribosomal RNA genes (rRNA), and a non-coding control region (D-loop). The percentage of A/T (65.59%) is much higher than that of C/G (34.41%). The phylogenetic tree revealed that R. ovatilabrum was closest to R. kanmonensi and R. periflaviceps. The mitochondrial genome of the R. ovatilabrum provides a resource for evolutional analysis within termites especially Reticulitermes.